Clones and Commodification: An Ethical Issue in Ishiguro’s Never Let Me Go - Sharma, Kamal; Joshi, Amrit Prasad (Literary Studies, 2025)
The paper explores an ethical concern of clones’ commodification in the novel Never Let Me Go, set during the late 1990s in England. It revolves dominantly around three clone characters; Kathy H, Tommy D and Ruth. Their initial position as happy students at a seemingly idyllic Hailsham school is erased when they are identified as clones. They are ostracized and excluded from society as the society does not acknowledge them as humans. Their unnatural birth creates more complexity of moral questions while fulfilling the selfish purpose of normal people. The mention of words/phrases like “guardians”, “carers”, “donors”, “completions”, “ractice” and “the Gallery” is a tactful strategy of the dominant humans, the creators, to put the clones in the position of painful servitude. Do clones exist to serve the humanity? Are they different to humans? Who owns these bodies?, are pertinent questions to discuss about the ethics of cloning and subsequent impacts on clones. Since clones are the victims, the ethical issues fall on the part of humans – the guardians. Clones’ meaningless life, in Agamben’s term, the bare life and their constant supervision in Hailsham similar to the concept of panopticon in Foucault term, raises the ethical issue of what it means to be human. The research follows textual analysis as research method within qualitative research design. It concludes that the clones’ state of servitude and their position of donors showcase commodification of clones and the inhumanity of humanity. It raises ethical and moral questions regarding advancements of medical science in which Kathy, Ruth and Tommy live.